Online Software Copyright Protection Using Trust Platform Module and Database Watermarking - Al-Kushari, Abdullah A.; Zahary, Ammar; Alkhawlani, Mohammed M. (University of Science and Technology, Yemen, 2014)
As the digital information can be copied and transmitted easily, new and novel methods for the investment safeguarding are highly important. Many software companies developed several ways to prevent their software from piracy but hackers are still working. Other companies have their own techniques, but they keep them for confidential. This paper utilizes the digital watermarking and the Trust Platform Module (TPM) to enhance software piracy protection and decrease the efforts costs to protect software copyrights. The paper conducts a new approach called Trust Platform Module and Database Watermarking (TPMDWM) which is developed to enhance the software copyright protection. The proposed approach combines the new technologies of Trust Platform Module with database watermarking, hash function, and advanced encryption standard to enhance software copyright protection and decrease the cost and loose of software revenues. As shown by results, TPMDWM can effectively prevent illegal copying, getting the software at installation or updating license. The results also show that TPMDWM approach does not affect the software code and control. In addition, TPMDWM decreases dongle cost and it can also be used for client identification.